Studies on Chemical Constituents of Caesalpinia bonduc L. Roxb - Sarah Mobasher,; Sumayya Saied,; Shaista Naz,; Juhi Khan, (Journal of Basic & Applied Sciences, 2014)
A new compound caesanol 1 and a known diterpene 6β, 7β-dibenzoyloxyvouacapen-5α-ol 2 is isolated for the first time from ethanolic extract of aerial part of this plant. Structures of both were elucidated on the basis of spectroscopic analysis.